2017
DOI: 10.1007/s11682-017-9764-1
|View full text |Cite
|
Sign up to set email alerts
|

Imaging behavioural complications of Parkinson’s disease

Abstract: In addition to motor symptoms, behavioural complications are commonly found in patients with Parkinson's disease (PD). Behavioural complications, including depression, anxiety, apathy, impulse control disorder and psychosis, together have a large impact on PD patient's quality of life. Many neuroimaging studies using PET, SPECT and MRI techniques have been conducted to study the underlying neural mechanisms of PD pathogenesis and pathophysiology in relation to its behavioural complications. This review will su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 96 publications
0
14
0
1
Order By: Relevance
“…The results showed a significant upregulation of TLR7 and TLR8, validating their involvement in the pathological process. It is well known that PD is characterized by a variety of behavioral deficits [43,44], resulting in a variety of symptoms concerning motor control, such as bradykinesia, rigidity, and tremor [45]. Anxiety symptoms are also very common in PD patients, and some authors state that anxiety in PD can be manifested even before the emergence of the first motor symptoms [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed a significant upregulation of TLR7 and TLR8, validating their involvement in the pathological process. It is well known that PD is characterized by a variety of behavioral deficits [43,44], resulting in a variety of symptoms concerning motor control, such as bradykinesia, rigidity, and tremor [45]. Anxiety symptoms are also very common in PD patients, and some authors state that anxiety in PD can be manifested even before the emergence of the first motor symptoms [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several anatomical and functional MRI studies in patients with Parkinson's disease with ICDs have shown dysfunctions in limbic and cortico-subcortical circuits engaged in risk-taking, reward-learning, reducing punishment learning and outcome evaluation as well as cognitive control difficulties (Santangelo et al, 2017). These abnormalities mostly consist of dysfunctions of the ventral striatum and cortico-limbic areas as well as abnormal connectivity between the mesolimbic and meso-cortical regions (Cilia et al, 2010;Rao et al, 2010;van Eimeren et al, 2010;Voon et al, 2011b;Politis et al, 2013;Cerasa et al, 2014;Piray et al, 2014;Biundo et al, 2015;Carriere et al, 2015;Claassen et al, 2017;Tessitore et al, 2017;Valli et al, 2017;Petersen et al, 2018). However, most of these studies have enrolled pa-tients with Parkinson's disease with either various forms of ICDS or only pathological gambling (Steeves et al, 2009;Cilia et al, 2010Cilia et al, , 2011Rao et al, 2010;van Eimeren et al, 2010;O'Sullivan et al, 2011;Voon et al, 2011bVoon et al, , 2014Joutsa et al, 2012;Ray et al, 2012;Politis et al, 2013;Cerasa et al, 2014;Piray et al, 2014;Vriend et al, 2014;Biundo et al, 2015;Carriere et al, 2015;Tessitore et al, 2017;Petersen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of epidemiological studies, patients with PD are more prone to developing anxiety disorders and taking anxiolytic drugs before a diagnosis of PD [48]. The prevalence of anxiety disorders in patients with PD is up to 60%, however, anxiety remains unrecognized due to the similarity of symptoms with a neurological disease and comorbidity with depressive disorders -92% of patients with PD with diagnosed anxiety showed a depressive disorder, and 62% of depressed patients with PD -Anxiety Disorder [11,30,49,50]. Such overlap of symptoms is explained by a common neurobiological substrate: degeneration of the subcortical nuclei, dopamine, noradrenergic and serotonin pathways in the circuits, involving the fronto-basal ganglia, with a specific loss of dopaminergic and noradrenergic innervation in the locus coeruleus and limbic system of the brain [51].…”
Section: Anxiety and The Spectrum Of Anxiety Disordersmentioning
confidence: 99%